2019
DOI: 10.1038/s41598-019-54726-6
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole-loaded 3D-printed bioceramic scaffolds stimulate pediatric bone regeneration in vivo without disruption of craniofacial growth through facial maturity

Abstract: This study investigates a comprehensive model of bone regeneration capacity of dypiridamole-loaded 3D-printed bioceramic (DIPY-3DPBC) scaffolds composed of 100% beta-tricalcium phosphate (β –TCP) in an immature rabbit model through the time of facial maturity. The efficacy of this construct was compared to autologous bone graft, the clinical standard of care in pediatric craniofacial reconstruction, with attention paid to volume of regenerated bone by 3D reconstruction, histologic and mechanical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 63 publications
(101 reference statements)
3
73
1
1
Order By: Relevance
“…They revealed a volumetrically and functionally significant osteogenic regeneration of calvarial defects, with a neoformed vascularized bone comparable to native tissue. Moreover, the Authors confirmed, using 3D morphometric facial surface analysis, that the 3D-printed β-TCP and dipyridamole scaffold does not lead to premature closure of sutures and allows to maintain the normal craniofacial growth [121].…”
Section: Tissue Engineering Strategiesmentioning
confidence: 84%
“…They revealed a volumetrically and functionally significant osteogenic regeneration of calvarial defects, with a neoformed vascularized bone comparable to native tissue. Moreover, the Authors confirmed, using 3D morphometric facial surface analysis, that the 3D-printed β-TCP and dipyridamole scaffold does not lead to premature closure of sutures and allows to maintain the normal craniofacial growth [121].…”
Section: Tissue Engineering Strategiesmentioning
confidence: 84%
“…This explains the increased popularity of vascularized autologous bone grafting as the standard option ( 62 ). Multiple reconstructive options have emerged for mandibular reconstruction, including iliac crest, rib and fibula ( 63 ). The fibula was first utilized by Hidalgo et al ( 64 ) for mandibular reconstruction in 1989.…”
Section: Discussionmentioning
confidence: 99%
“…3D Printing of Bone Biomimetic Scaffolds Ceramics have been commonly used for the 3D printing of bone tissue engineering scaffolds [36][37][38][39][40][41][42][43]. This is due to their inorganic composition, high stiffness, hydrophilicity, bioactivity, biocompatibility, and osteoconductivity, which make it an ideal material to generate a biomimetic scaffold [36].…”
Section: Print-and-implant Strategies That Harness Bone's Inherent Reparative Capacitymentioning
confidence: 99%